Modeling Effective Budgeting and Production For Sustainable Competitive Advantage: Evidence from Kufa Cement Factory, Iraq - ALAWAED Husam Muhammed Ali; AL-KAWAZ Salah Mahdi Jawad; ABBAS Ali Abdulhassan; ALNASRAWI Salam Adil Abbas (Foundations of Management)
The current study aims at conceptualizing time-driven activity-based budgeting and cleaner production (CP) techniques and their integration in achieving sustainable competitive advantage by applying them at Kufa Cement Factory, an economic unit under the Iraqi Ministry of Industry. The research reached several crucial conclusions. Two techniques are integrated as a hybrid model based on time-driven activity budgeting with CP for the reciprocal relationship between contemporary management accounting techniques. This model gets rid of environmental problems, identifies idle energy as output from the time-driven activity-based budget, and uses it for increasing the production, sales, and profitability. The most important recommendation is that strategic thinking should be leveraged for economic unit management and competitive advantage as it is characterized by strong insights, environmental sensing, etc. It can analyze and interpret the information and has a comprehensive knowledge on various aspects of the economic unit and its requirements. The strategies must be defined to leverage the manpower and resources and translate the goals into victory.